The interplay between protein phosphorylation and ubiquitylation in the NF-κB pathway - Chen, Zhijian 'James' (Henry Stewart Talks, 2010)
Ubiquitination is a reversible covalent modification, akin to phosphorylation, Ubiquitination regulates protein kinase activity through proteasome-independent mechanisms, K63-linked polyubiquitination activates TAK1 and IKK in the NF-kappaB pathway, Deubiquitination enzymes inhibit protein kinases in the NF-kappaB pathway, Protein kinase regulation by ubiquitin is important in innate and adaptive immunity